FINANCIAL LITERASI, PERILAKU KEUANGAN SEBAGAI PEMBENTUK FINANCIAL CAPABILITY PADA UKM KREATIF DI SULAWESI SELATAN - Sarira, Simeon; Kadir, Abd Rahman; Saudi , Nur Dwiana Sari (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
This study aims to analyze and explain how Financial Literacy and Financial Behavior form financial capabilities in Creative SMEs in South Sulawesi. The type of research that will be used in this study is the Explanatory Type. This research is a causality research where there is a causal relationship between two or more variables. The questionnaires distributed in this study were 100 and the response rate was 100% and the questionnaires that were feasible to analyze were 100 questionnaires. The method of data analysis in this study is multiple linear regression analysis (Multiple Regression Analysis). The research data was processed using the Statistical Package for Social Science (SPSS) program. By using data collection techniques using a questionnaire. The results of this study indicate that Financial Literacy and Financial Behavior have an influence in shaping the financial capabilities of Creative SMEs in South Sulawesi.